Assessment of local tissue water in breasts following breast reconstruction with an expander prosthesis or DIEP flap. Issue 4 (1st August 2022) - Tallroth, Linda; Brorson, Håkan; Mobargha, Nathalie; Velander, Patrik; Klasson, Stina; Becker, Magnus
Abstract: The role of breast oedema in breast reconstruction is unknown. Therefore, our aim was to investigate local tissue water (LTW) and breast oedema-related symptoms in breasts reconstructed with either an expander prosthesis (EP) or with a deep inferior epigastric perforator (DIEP) flap at a minimum of one year postoperatively. Sixty-eight patients randomised to breast reconstruction with an EP or DIEP flap completed follow-up. Objective evaluation was performed at a mean of 25 (standard deviation, SD 9.5) months following breast reconstruction, and included measurements of breast volume and LTW with the MoistureMeterD® instrument. The patients completed the BREAST-Q questionnaire pre- and postoperatively. No significant differences in LTW were found when comparing EP and DIEP flap reconstructed breasts. The reconstructed breasts had an increase in LTW compared with the non-operated contralateral breasts. The BREAST-Q responses related to breast oedema symptoms were overall low and the median responses ranged from 1 to 2. A score of 1 indicated that symptoms were experienced 'None of the time'. Our findings indicate that mastectomy followed by breast reconstruction inflicts damage on the lymphatic system, shown as an increase in LTW. However, no breast oedema-related symptoms were reported in the BREAST-Q questionnaire, and therefore, we consider our objective results to be below a potential threshold for symptomatic breast oedema. A threshold for clinical indication of breast oedema remains to be defined.